The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jor.2018.08.034
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of intra-operative hamstring autograft size with pre-operative anthropometric and MRI measurements

Abstract: The purpose of this study was to compare various pre-operative methods of estimating intra-operative hamstring autograft size. A retrospective review was completed on 74 patients who had an anterior cruciate ligament reconstruction performed using a quadruple-looped hamstring autograft from July 2007-April 2015 at a single institution. A positive correlation was observed between intra-operative graft size and pre-operative imaging using two methods of MRI measurements. Correlation existed between hamstring siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Our study, much like several other studies, confirms many of these findings. 19 , 22 This study found that increased height, increased weight, and male sex correlated with an increase in graft size. Unlike in previous studies, BMI was not statistically significant in our cohort.…”
Section: Discussionmentioning
confidence: 80%
“…Our study, much like several other studies, confirms many of these findings. 19 , 22 This study found that increased height, increased weight, and male sex correlated with an increase in graft size. Unlike in previous studies, BMI was not statistically significant in our cohort.…”
Section: Discussionmentioning
confidence: 80%
“…Authors of 2 studies suggested that patient height, weight, and thigh circumference were correlated with hamstring graft diameter. 1 , 5 In other words, a taller, heavier patient may have a thicker hamstring graft compared with a lighter, shorter patient, but grafts of both patients may still be smaller than 8.0 mm when the conventional 4HS technique is used. Moreover, those 2 studies relied on MRI measurements and/or equations that we had difficulty applying in our high-volume setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies on preoperative prediction using anthropometry, most of the research subjects are European and American; only a small proportion are Asian, and there are no such studies involving Chinese people. 12,16,17,[22][23][24][25][26][27] In this study, the Zhuang population, the largest minority in China, is selected as the study population to examine the feasibility of using preoperative ultrasound and anthropometric data to predict the final graft diameter before ACL reconstruction with 4 S-STG.…”
Section: Backg Rou N Dmentioning
confidence: 99%